Service-oriented network architecture: significant issues and principles of communication. (2015) - Rudra, Bhawana; Manu, A.P.; Vyas, O.P.
The internet is not designed for any specific application purposes, rather it is for generic and evolve purposes. Although the architecture of the internet is based on a number of principles including self-describing, datagram packet, the end-to-end argument, diversity in technology, and global addressing, but David D. Clark along with J.H. Saltzer highlighted end-to-end arguments amongst the most influential of all the communication protocol design goals. Also that internet adopted a method of patchwork approach to cope with the needs of evolution and revolution of technology growth with acceptable cost and speed. The future network is expected to host much more than today's applications in an efficient manner but experts predicted rigidity as one of the failure factors for current internet (CI). In this paper the authors discuss various issues involved in the flexible network architecture - SONATE (Reuther and Henric, 2008) while incorporating security functionality 'inside' the architecture.